Comparing the natural progression and clinical features of keratoconus between pediatric and adult patients - Ken-Kuo Lin; Yun-Wen Chen; Chun-Ting Yeh; Pei-Ru Li; Jiahn-Shing Lee; Chiun-Ho Hou; Ching-Hsi Hsiao; Lai-Chu See (Scientific Reports, 2022)
Abstract To present the natural course of keratoconus (KC) and compare pediatric and adult patients. Design A retrospective cohort study. Setting Hospital-based. Patient Population In total, 152 patients (288 eyes) diagnosed with KC at Chang Gung Memorial Hospital, Taiwan, were included. Previously managed patients and those with missing optical data were excluded. Observation Procedures Patients were divided into pediatric (≤ 18 years) and adult (> 18 years) groups. Demographics, clinical data, and optical variables were collected, including corrected distance visual acuity (CDVA), refractive error, and keratometric readings (K). Main Outcome Measure Optical variables at the final follow-up before aggressive treatment. Results In total, 20 pediatric (37 eyes) and 132 adults (251 eyes) patients were eligible for this study. The mean follow-up time was 2.98 years. Male predominance was observed in both groups. Both groups had similar clinical characteristics and optical variables at the initial diagnosis. Pediatric patients progressed significantly more rapidly in refractive errors, including spheres and cylinders, spherical equivalence, steep K, and flat K during the follow-up. However, significant change between the two study groups was only seen in sphere refractive error spherical equivalence. Conclusion Pediatric patients had more rapidly progressive KC than adult patients, so early detection and frequent follow-up for prompt interventions are necessary for these patients.